2015
DOI: 10.1093/nar/gkv666
|View full text |Cite
|
Sign up to set email alerts
|

Sense and antisense transcription are associated with distinct chromatin architectures across genes

Abstract: Genes from yeast to mammals are frequently subject to non-coding transcription of their antisense strand; however the genome-wide role for antisense transcription remains elusive. As transcription influences chromatin structure, we took a genome-wide approach to assess which chromatin features are associated with nascent antisense transcription, and contrast these with features associated with nascent sense transcription. We describe a distinct chromatin architecture at the promoter and gene body specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
114
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(126 citation statements)
references
References 55 publications
12
114
0
Order By: Relevance
“…S5C,D). This is consistent with recent observations showing that H3 acetylation is high along genes with antisense transcription in S. cerevisiae (Murray et al 2015).…”
Section: Expression Of Asxuts Is Associated To Specific Patterns Of Hsupporting
confidence: 94%
“…S5C,D). This is consistent with recent observations showing that H3 acetylation is high along genes with antisense transcription in S. cerevisiae (Murray et al 2015).…”
Section: Expression Of Asxuts Is Associated To Specific Patterns Of Hsupporting
confidence: 94%
“…Furthermore, mathematical models of transcriptional interference by Sneppen et al 15 have shown that in order for transcription in one direction to impact transcription in the opposite direction, very high levels of transcription are required, possibly above what is typically observed. In Murray et al 9 we demonstrate that antisense transcription is not correlated with sense transcription genome-wide, either positively or negatively. This lack of correlation remained when considering only subsets of genes with different levels of antisense transcription.…”
Section: Antisense Transcription Is Not a Universal Repressor Of Sensmentioning
confidence: 52%
“…9 Based on this, and the abundant nature of antisense transcription genome-wide, 4 we propose that antisense transcription should be considered a canonical feature of genes, as opposed to an idiosyncrasy particular to just a subset of genes. Future work should seek to understand the function of the dynamic chromatin established by antisense transcription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations